Use of Cardio-Pulmonary Ultrasound in the Neonatal Intensive Care Unit - Elena Ciarmoli; Enrico Storti; Jessica Cangemi; Arianna Leone; Maria Pierro (MDPI AG, 2023)
Cardiopulmonary ultrasound (CPUS), the combination of lung ultrasound (LUS) and targeted neonatal echocardiography (TnECHO)AA, may offer a more appropriate approach to the challenging neonatal cardiovascular and respiratory disorders. This paper reviews the possible use of CPUS in the neonatal intensive care unit (NICU).